Extreme scale-dependent tensile properties of epoxy fibers - X. M. Sui; M. Tiwari; I. Greenfeld; R. L. Khalfin; H. Meeuw; B. Fiedler; H. D. Wagner (eXPRESS Polymer Letters, 2019)
Epoxy fibers with different diameters were prepared by hot drawing and their mechanical properties were measured under tension. The stiffness, strength, ultimate strain, and toughness revealed substantial scale-dependent effects as they all significantly increased with a decrease in size. Compared to bulk epoxy, an intrinsically brittle material, thin epoxy fibers displayed a highly ductile behavior under tension. A drop in stress observed immediately beyond the yield point was followed by the development of a stable necking region propagating through the entire fiber length, then by strain-hardening up to final rupture. Necked fiber segments tested in tension were found to have even higher strength and modulus compared to the initial as-prepared fibers. Possible reasons for the highly ductile mechanical behavior and the size effects of epoxy fibers are discussed. Size effects for the strength of epoxy can be elucidated in principle either by means of a classical fracture mechanics argument (strength ~ 1/d1/2), or via a stochastic model argument (strength ~ 1/d1/β, where β is a function of the material and is generally larger than 2). In both models the presence and size of critical defects play a key role. However, defects cannot explain the colossal ductility (plastic deformation) seen in our experiments, nor can the presence of defects justify a size effect in an elastic property, namely Young’s modulus. Only scarce evidence exists in the literature for similar (milder) size effects in epoxy fibers but without any structural justification. We find here that highly cross-linked necked epoxy fibers exhibit partial macromolecular anisotropy which likely explains the observed high mechanical characteristics.